2002
DOI: 10.1016/s0893-133x(01)00413-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptidic δ-opioid Receptor Agonists Reduce Immobility in the Forced Swim Assay in Rats

Abstract: The present study examined the effect of opioid receptor agonists in the rat forced swim assay. The ␦ -opioid receptor agonists SNC80 (( ϩ )-4-[( ␣ R)-␣ -((2S,5R)-4-Allyl-2,5-dimethyl-1-piperazinyl)-3-methoxybenzyl]-N,Ndiethylbenzamide) and ( 7 ␣ ,5]classes of compounds have also been investigated and have potential antidepressant activity. One such class of agents is the opioids. Studies have been performed using a variety of different opioid system-enhancing agents that suggest an antidepressant role for opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 18 publications
14
122
2
Order By: Relevance
“…, a drug that has antidepressant-like actions in rodent models (22). In contrast with our observations using monoaminetargeting antidepressants, Rgs4KO mice respond better to SNC80 in the forced swim test than their wild-type controls (Fig.…”
Section: Resultssupporting
confidence: 40%
“…, a drug that has antidepressant-like actions in rodent models (22). In contrast with our observations using monoaminetargeting antidepressants, Rgs4KO mice respond better to SNC80 in the forced swim test than their wild-type controls (Fig.…”
Section: Resultssupporting
confidence: 40%
“…We examined the effect of agonist treatment on the distribution of subcellular DOR-EGFP fluorescence in the knockin mice. We treated DOR-EGFP mice with either vehicle or SNC80 (10 mg͞kg s.c.), known to induce ␦ receptor-mediated behaviors (29,30). After 20 min, brains were removed, and receptor distribution was examined in six areas of the nervous system including central and peripheral sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be proposed that an increased d-opioid receptor activity by NDMC may contribute, at least in part, to the reported clinical efficacy of clozapine in ameliorating psychotic mood disorders (McElroy et al, 1991), in reducing the risk of suicide in schizophrenia and schizoaffective disorder (Meltzer et al, 2003;Kerwin and Bolonna, 2004) and in suppressing aggressive behaviors in psychotic patients (Kraus and Sheitman, 2005). A relevant role of dopioid receptors in depression is further supported by pharmacological data showing that the nonpeptidic dopioid receptor agonists ( + )BW373U86 and SNC80 exerted antidepressive effects in animal models (Broom et al, 2002) and potentiated D 1 and D 2 DA receptor stimulation (Spina et al, 1998), which may improve cognition and depression, and that, conversely, d-opioid receptor antagonists caused anxiety-related behaviors (Saito et al, 2005). Like antidepressant drugs (Nibuya et al, 1995), d-opioid receptor agonists have been found to increase the hippocampal and cortical synthesis of brain-derived neurotrophic factor (BDNF) (Torregrossa et al, 2004), which is known to regulate neuronal development and plasticity and has been shown to possess antidepressant activity (Shirayama et al, 2002).…”
Section: Discussionmentioning
confidence: 96%